POVERTY AND THE CHALLENGES OF INSECURITY TO DEVELOPMENT - Ajodo-Adebanjoko, Angela; Walter, Ugwuoke Okwudili (European Scientific Journal, ESJ, 2014)
Poverty and insecurity are twin problems of development in Nigeria. Poverty is a major problem in Third World countries in general and in particular Africa to which Nigeria belongs. The poverty level in Nigeria is such that many people live below the poverty line. The economic growth in the nation’s GDP has not translated to reduction of the number of people living below poverty line. The poverty level in Nigeria has become worrisome and the subject of growing attention by academics and policy makers. Though poverty reduction has become the major goal of the government, much is yet to be done. Insecurity is also rife in many parts of the country with people dying on a daily basis from factors which are political, strategic, economic, social, or ecological nature. Poverty in the country is more pronounced in conflict-prone areas while insecurity is rife in poverty-stricken areas which generate the question of the relationship between poverty and insecurity as well as their implications for development. The objectives of this paper therefore were to find out if poverty is the effect as well as a cause of insecurity and the implication of this for development. The paper examined the relationship between poverty, conflict and insecurity in Nigeria with particular reference to conflict-ridden areas of the North-East, South-South and Middle-Belt. Secondary sources of data were used and data were taken from the National Bureau of Statistics (NDS). Research findings show that insecurity contributes to poverty with implications for development and the need to shun violence was recommended.